The Impact and Direction of National Standardized Sentencing Reform in China - Xiaoqin, Ye (Columbia Journal of Asian Law, 2011)
On October 1, 2010, the People’s Republic of China (“China”) implemented nationwide reform to standardize criminal sentencing in the form of two landmark judicial documents with the goal of reducing unwarranted sentencing disparities and establishing relatively independent sentencing procedures. On that date, all Chinese courts implemented the Directive on Sentencing in the People’s Courts (for Trial Implementation) (“Directive on Sentencing”),’ promulgated by the Supreme People’s Court (“SPC”); and the Opinion on Certain Issues of Standardized Sentencing Procedure (for Trial Implementation) (“Opinion on Sentencing Procedure”),’ promulgated by the “Two Supremes” and “Three Ministries.”‘ These “guidance” documents, which provide strict standards and specific procedures for criminal sentencing, triggered full-scale “standardized sentencing reform” ( A M 011 r *) (liangxing guifanhua gaige) throughout the Chinese court system. This article briefly discusses the primary impact and possible implications of these new reforms, in particular the Directive on Sentencing. The Directive on Sentencing and Opinion on Sentencing Procedure have no legally binding effect. Of course, these standardized sentencing rules would enjoy stronger legal effect if promulgated as laws by the National People’s Congress (NPC) or as a judicial interpretation by the SPC, as authorized by the Standing Committee of the NPC. Specific sentencing rules can be seen as applying the penalty range provisions of the Criminal Law. It is usually the NPC that promulgates and amends basic laws such as the Criminal Law and the Criminal Procedure Law, and the SPC itself seems not to have gained sufficient experience to enact a complete judicial interpretation on sentencing issues for all offenses. But apparently the SPC thinks it necessary to promote sentencing reform at present, relying on Article 127 of the Constitution of the People’s Republic of China to promulgate the Directive on Sentencing.’ Article 127 authorizes the SPC to supervise trials in local courts and authorizes higher courts in general to supervise trials in lower courts. The SPC’s guidance on sentencing, then, can be understood as a means of supervising criminal trials at all levels. So the Directive on Sentencing and Opinion on Sentencing Procedure are designated as pilot judicial documents without binding force: they provide only supervisory guidance in sentencing, and a more formal set of 6 rules is to be enacted after sufficient data on sentencing are collected.